ASOSIASI ANTARA POLUSI UDARA DENGAN IgE TOTAL SERUM DAN TES FAAL PARU PADA POLISI LALU LINTAS - Fahimi, Mukti; Dharma S, Bayu; Fetarayani, Deasy; Baskoro, Ari; Soegiarto, Gatot; Effendi, Chairul (journal of internal medicine, 2014)
Ambient air pollution often associated with allergic diseases and impaired respiratory function. Total serum IgE levels was  one  of  the  diagnostic  tools  to  establish  an  allergic  diseases while  lung  function  test was  standard  examination to establish alteration in lung function. Trafc police ofcers were often assigned on the highway is one of the most vulnerable population against exposure to air pollution. Aim of this study isto know the association between air pollution on total serum IgE levels and lung function in trafc police ofcers compared to staff police ofcer as control.This is an observational analysis study with cross sectional design.There were 60 police ofcers as a subject, divided in two groups. Thirty subjects as exposured groups and 30 subjects as control group. Air pollution was measured by Pollutant Standard Index (PSI)/ Indeks Standar Pencemar Udara (ISPU) method. Independent  t-test and Mann-Whitney  test were used  to analyze differences between variabel. Spearman test was used to analyze correlation and strength between variabel.There were no signicant differences in total IgE serum levels between groups (p = 0.301). There were signicant differences in FEV1 (%p) (p = 0.015), FVC (%p) (p = 0.000) and spyrometry result (p = 0.001). There was no signicant difference in FEV1/FVC ratio (p = 0.573). There were negative weak association between air polution and FEV1 (%p) (r = -0.298; p=0.021) and between air pollution and spyrometry result (r = -0.380; p = 0.003). There was negative moderate association between air pollution and FVC (%p) (r = -0.409; p = 0.001). There was no association between air pollution and FEV1/ FVC ratio (r = 0.058; p = 0.662). There was signicant association between air pollution and impaired respiratory function but there was no association between air pollution and total serum IgE levels.
Keywords: Air pollution, PSI, trafc police ofcer, total serum IgE, lung function